EXPLORING GAMIFICATION AND USER BEHAVIOUR OF PLAYER UNKNOWN BATTLE GROUND GAME (PUBG) GAMERS IN MANADO - Mandagi, Yosua Leonardo; Tulung, Joy E.; Pandowo, Merinda H. C. (Universitas Sam Ratulangi, 2020)
Abstract: Gamification is the application of game features, mainly video game elements, into non-game context for the purpose of promoting motivation and engagement in non-gaming situation. With gamification, game creators and game developers can shape user behaviour of gamers that they become addicted. This study investigates gamification and user behaviour on PUBG mobile game (PUBG gamers) in Manado. The research method is qualitative analysis with interview technique. The sample size is 15 respondent using purposive sampling technique. The results show that most gamers are between 16-32 years old because almost all the games have a high level of difficulty which is so challenging and hard indeed for people below 16 and above 32 years old and PUBG game has various techniques of gamification that influence how the gamers want to keep playing. It is recommended that game developers need to study deeper about gamification to improve engagement for the users.Â Keywords: Gamification, User Behavior, Game Player, Game Element, Dynamics, Mechanics, Components, Psychology, Sociology, Behavioral Economics.